Bilateral Facial Nerve Palsy After Weekly Nanoparticle Albumin–Bound Paclitaxel Treatment in Pancreatic Cancer - Vishal Yalamanchili; Ronald Harris (Annals of Internal Medicine: Clinical Cases)
Peripheral neuropathy is a common side effect of microtubule inhibitors. Rare cases of cranial nerve palsies have been reported with paclitaxel and 1 case of unilateral facial nerve palsy has been reported with nanoparticle albumin-bound paclitaxel (nab-ptx). We report a rare case of bilateral facial nerve palsy from nab-ptx.